Analisis Sistem Pengendalian Internal Pada Lembaga Amil Zakat Al Azhar - Andrean Muhammad Anwar; Krisno Septyan (WIDYAKALA: JOURNAL OF PEMBANGUNAN JAYA UNIVERSITY, 2019)
This study aims to analyze the implementation of the internal control system in the collection process until the distribution of zakat funds in this study was conducted at the Al Azhar Amil Zakat Institution, this research is a qualitative research using a phenomenological approach. Based on the results of this study revealed that the Amil Al Azhar Institution in 1) The control environment in the aspect of integrity and ethical values always emphasizes the standards determined by the center. 2) Risk withdrawal is carried out with each transaction known to the Branch Leader and inputted using the system then for internal changes such as the presence of new employees and the risk assessment. 3) Control activities are carried out by ensuring that the quality of transaction authorization is guaranteed by donors coming to the office for transactions to always fill in the proof of deposit. Good safeguards for assets and independent checks are carried out every few months. 4) Information and communication is carried out by always using the custumer service and internal information systems. There is good communication between divisions. 5) Monitoring mechanism is carried out by monitoring internal and external partiesKeywords: Internal Control, Zakat Collection, Zakat Distribution